Without reasons ; Disabled not unable ; Ang Bohemya [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Investigates the murder of three teenage boys. Tackles disabled people from the respected members of society. Rolando Tinio translating La Boheme and adapting it to stage setting.
Contents : Without reasons (17 min.) -- Disabled not unable (15 min.) -- Ang Bohemya (17 min.).
VHS
Keywords: Murder -- Philippines; Handicapped -- Philippines; La Boheme -- Adaptations